COMPARISON OF SHARIA GOVERNANCE MODEL IN ISLAMIC FINANCIAL INSTITUTIONS BETWEEN THE GCG AND ASIAN COUNTRIES - Izzani Ulfi (Asosiasi Dosen Muda Indonesia, 2022)
Sharia governance is one of the fundamental characteristics that differentiate Islamic and conventional financial institutions. Therefore, the understanding related to sharia governance in Islamic financial institutions such as Islamic banking becomes significant. By using a literature study approach, this paper aims to review and compare regulations related to Islamic financial governance in GCG and ASIA countries. The result shows that the GCC countries and the Asia model of Sharia Governance are a huge difference. The GCC countries use the minimalist model of Sharia governance whereas Asian countries still use the interventionist model. The similarity in this term is about the fundamental of the regulations, which are based on the Quran and Hadith.